Conversion of soy industry waste into useful materials - Lee, Yean Huar (2019)
Okara, the insoluble residue of soybean after generating food products like miso, tofu and soymilk is discarded in a tremendous amount daily. This phenomenon has caused a serious disposal problem not only in Singapore but worldwide. The aim of this study is to transform this foul- smelling but nutrient-rich product into biodegradable thin film matrix that may serve as an alternative to the conventional plastics in food packaging. High-molecular weight polysaccharides are extracted from the Okara waste using two methods: (1) sonication and (2) ethanol precipitation. For extraction using the sonication method, various conditions were conducted such as modifying the concentration of Okara solution (1.0% w/v to 10.0% w/v), changing the types of sonicators (bath sonicator and probe sonicator) and altering the duration of sonication (1 hour to 8 hours). The highest yield generated from the sonication method was 21.18% while using the ethanol precipitation method resulted in a higher yield at 32.26%. The extracted high-molecular weight polysaccharides were mixed with glycerol to produce the final product - an Okara film with 60mm (length) * 17.77 mm (width) * 0.28mm (thickness) using the Collin P 500 Press. Characterization tests including FTIR, DSC, TGA, SEM imaging, tensile testing were conducted on the Okara film. Results show that the ultimate tensile strength of the film is 2.22MPa and this can be modified by altering the amount of glycerol added as it provides greater plasticity and elasticity to the film.